Islamic Economy in Supporting Community Resilience Through Business Assistance Programs - Isti Nuzulul Atiah; Sahraman D. Hadji Latif (Government & Resilience, 2025)
This study examines the impact of empowerment programs and business assistance on mustahiq welfare in Amil Zakat Institutions in Banten, with business growth as a mediating variable. A total of 160 respondents who have participated in the empowerment program were selected for analysis. This study uses the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach to test the relationship between these variables. There is a significant influence between zakat empowerment on mustahiq welfare, business assistance on mustahiq welfare, and business assistance on business development, while business development on mustahiq welfare and zakat empowerment on business development do not have a significant influence. The need to increase the Zakat empowerment program is considered very important because Zakat empowerment can improve the welfare of mustahiq up to 27.1%. However, the contribution of business growth to mustahiq welfare is structurally still low. Nevertheless, increasing business growth is still considered important because it can improve mustahiq welfare.